Memory and Manuscript: Oral Tradition and Written Transmission in Rabbinic Judaism and Early Christianity - Birger Gerhardsson; Eric J. Sharpe 1933-2000; Jacob Neusner (Sweden C. W. K. Gleerup Denmark Ejnar Munksgaard, 1964)
In Memory and Manuscript (1961), Gerhardsson explores the way in which Jewish rabbis during the first Christian centuries preserved and passed on their sacred tradition, and he shows how early Christianity is better understood in light of how that tradition developed in Rabbinic Judaism. In Tradition and Transmission in Early Christianity (1964), Gerhardsson further clarifies the discussion and answers criticism of his earlier book. This Biblical Resource Series combined edition corrects and expands Gerhardsson's original works and includes a new preface by the author and a new foreword by Jacob Neusner that summarizes these works' importance and subsequent influence. --from publisher description
Tradition and transmission in early Christianity . With, Tradition and Transmission in Early Christianity
First work originally published: Lund, Sweden : C.W.K. Gleerup ; Copenhagen, Denmark : E. Munksgaard, c1961. (Acta Seminarii Neotestamentici Upsaliensis ; 22); 2nd work originally published: Lund, Sweden : C.W.K. Gleerup ; Copenhagen, Denmark : E. Munksgaard, c1964. (Coniectanea Neotestamentica ; 20). With new preface
Keywords: Holy Bible References (3GdcJGH GdebOS(B: (3eQGLYs; Bible -- History and criticism; Rabbinical literature; Tradition (Judaism); Transmission of texts; Tradition (Theology)